Dependence of the Translator’s Idiosyncrasy on the Writer’s Idiostyle (Linguostylistic Studies, 2021)
The idiosyncrasy of a translator, who translates belles-lettres works, must be well-coordinated with the author’s idiostyle. The text undergoes various transformations in the process of translation as it is re-coded into another language. The semantic dominant or its invariant peculiarities of the literary text should remain unchanged in the target language. Invariant includes both formal and meaningful elements of the text. Using the text of the novel "Widnokrąg" written by Wiesław Myśliwski as a case study of the research, we have identified its invariants which mainly comprise stylistic and linguistic means used to reproduce colloquial language. Actually, the study has revealed colloquial lexical units and, occasionally, phonetic-grammatical elements, as well as a particular syntax of Wiesław Myśliwski's idiostyle. Mostly, they are the stylistic means of mixing direct and indirect speech. Such elements of the text are not to be neglected and should be preserved in the text of translation to convey to the Ukrainian reader the author’s individual style feature. The contrastive analysis of the original text and the translation, applied by the author of the article, allows concluding that the translator managed to convey the majority of invariant’s means without losses. Even though some colloquial lexemes were sometimes translated with neutral Ukrainian equivalents, the translator tried to use the translation procedure of compensation close to the context, using the appropriate colloquialism of the target language. The author of the article also identifies the following issue as an element of semantic dominance. It is the wordplay of the author of the novel regarding the semantics of the keyword Widnokrąg, derived from a dichotomy of the colloquial and neutral word. The study focuses on various linguistic tropes, which elucidate the mystery of the language ontology and its various functions in a metaphoric manner.
Keywords: literary translation; semantic dominant; invariant; colloquial language; Wiesław Myśliwski